Hermite–Hadamard-type inequalities arising from tempered fractional integrals including twice-differentiable functions - Hezenci, Fatih; Budak, Hüseyin; Latif, Muhammad Amer (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We propose a new method for the investigation of integral identities according to tempered fractional operators. In addition, we prove the midpoint-type and trapezoid-type inequalities by using twice-differentiable convex functions associated with tempered fractional integral operators. We use the well-known Hölder inequality and the power-mean inequality in order to obtain inequalities of these types. The resulting Hermite–Hadamard-type inequalities are generalizations of some investigations in this field, involving Riemann–Liouville fractional integrals.